Pengaruh Perilaku Pegawai, Disiplin Kerja dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Unit Pengelola Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kelurahan Klender - Retnani , Rury; Muchtar , Hidayat (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
This research aims to analyze and evaluate the effect of employee behavior, work discipline, and service quality on public satisfaction at the Investment Management and Integrated One-Stop Service Unit of Klender Sub-district. The research method uses a quantitative approach through a questionnaire distributed to service recipients at the Investment Management and Integrated One-Stop Service Unit of Klender Subdistrict during the period of January - October 2024. The sample determination was formulated using the Slovin formula, resulting in a sample of 93 respondents. The data collected were analyzed using the IBM SPSS statistical program. The research results indicate that, partially, employee behavior has a significant effect on public satisfaction at 26.6%, work discipline has a significant effect on public satisfaction at 23.8%, and service quality has a significant effect on public satisfaction at 29.4%. Simultaneously, these three variables significantly affect public satisfaction by 41%, with the remaining 59% affected by other variables outside the scope of the research.